If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + 9 + x = -3 + 12 Combine like terms: -14 + 9 = -5 -5 + x = -3 + 12 Combine like terms: -3 + 12 = 9 -5 + x = 9 Solving -5 + x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = 9 + 5 Combine like terms: -5 + 5 = 0 0 + x = 9 + 5 x = 9 + 5 Combine like terms: 9 + 5 = 14 x = 14 Simplifying x = 14
| 13.2k+4.46=-16.06-9.6k | | 2(6n-5)=26+6n | | 4m+6n+8= | | 5b-3-11b-5= | | 19+t=2t | | 2d-6=7f+24 | | x^2-4x-656= | | 8.1x+1.25=-11.9+10.3 | | 9=8y-7y+3 | | 6x+x^2+8=0 | | (7y^2-7y-7)-(4y^2+2y+3)= | | 12+x-15=y+((x+12)-(x-15)) | | M+2m+3m=12 | | 2(t+1)= | | -17b-0.97=-14.88-19.8b-14.65 | | (w*98)=115(x) | | 7w+3d=-12 | | 5y-4y+2=-5 | | 10n+12-9-7n+4n=16+15 | | 11g+3-5g=39 | | 5(4c-1)-5=18c+8 | | 5y+4a=13 | | 20+14z=11z-20-8 | | -185=-32+17r | | 4s+1k=3r | | 13n=69 | | 11x+24=-2 | | 8z+7=-5z-57 | | 8-n=-4+2(4-n) | | 5.25q-2(3q+1.25)=q+1 | | 4s+k=3r | | 9.2s=12.8s-3.96 |